Imaging Findings of Ovarian Adenofibroma in Multiparous Woman - Sangavi Jeyaraj; Jaya Selin Praveena Joseph; Ashok Ranjan; Senthil Kumar Aiyappan (Journal of Clinical and Diagnostic Research)
A 29-year-old married, non pregnant multiparous woman presented to the Gynaecological Outpatient Department (OPD) with complaints of bilateral dull, aching lower abdominal pain of one year’s duration, more pronounced on the right side, which had aggravated over the past five days. There was no history of nausea or vomiting, and her menstrual cycle was regular, lasting three to four days every 28 days. She had a previous history of appendectomy eight months ago. Apart from this, her past medical history was unremarkable, and there was no family history of malignancy. Her general condition was fair, and her vitals were normal, with a blood pressure of 110/70 mmHg and a pulse rate of 82 beats per minute.